2015
DOI: 10.1016/j.indcrop.2015.03.057
|View full text |Cite
|
Sign up to set email alerts
|

Feeding and oviposition of Anticarsia gemmatalis (Lepidoptera: Noctuidae) with sublethal concentrations of ten condiments essential oils

Abstract: The experimental determination of petrophysical properties for shale rocks is dependent on measurement techniques and often produces inconsistent results. Alternatively, high-resolution three-dimensional imaging techniques coupled with image analysis and direct numerical simulations have been employed to estimate these parameters in shale samples. Nevertheless, the application of these results at the core and reservoir scales are uncertain due to the limited size of imaged samples. Here, Focused Ion Beam milli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 63 publications
0
21
0
1
Order By: Relevance
“…The results showed that the most abundant compound was terpinen-4-ol (40.09%), revealing that the essential oil was a chemotype of high terpinen-4-ol oil. In the antifeedant assay, the essential oil had a pronounced antifeedant effect, but exhibited lower level of antifeedant compared with other essential oils in previous studies (Abdullah et al, 2015;Quesada-Moraga, Carrasco-Diaz, & Santiago-Alvarez, 2006;Ribeiro et al, 2015). Notably, the constituents of terpinen-4-ol had distinctly deterred feeding activity on H. armigera, which is well worth further research and development.…”
Section: Discussionmentioning
confidence: 70%
“…The results showed that the most abundant compound was terpinen-4-ol (40.09%), revealing that the essential oil was a chemotype of high terpinen-4-ol oil. In the antifeedant assay, the essential oil had a pronounced antifeedant effect, but exhibited lower level of antifeedant compared with other essential oils in previous studies (Abdullah et al, 2015;Quesada-Moraga, Carrasco-Diaz, & Santiago-Alvarez, 2006;Ribeiro et al, 2015). Notably, the constituents of terpinen-4-ol had distinctly deterred feeding activity on H. armigera, which is well worth further research and development.…”
Section: Discussionmentioning
confidence: 70%
“…In this way, insecticide sublethal doses/concentrations may present deterrent effect for insect oviposition and feeding. Sublethal concentrations of several essential oils caused the reduction in feeding and oviposition of A. gemmatalis by the presence of essential oil volatile components that modified the insect behavior [26]. Sublethal doses of methomyl promoted behavioral disruption of S. littoralis for food odors [27].…”
Section: Insect Behavior As a Measurement Of Insecticide Sublethal Efmentioning
confidence: 99%
“…This oil is used to control this mite, but it should be applied at suitable times (large infestations) and with the doses recommended to avoid or reduce the impact on the hive. The toxic concentration of this product to T. hyalinata and A. mellifera was higher than that recommended for the control of the pests A. gemmatalis (LC 25 = 0,41%) 14 , Choristoneura rosaceana (Lepidoptera: Tortricidae) (LC 50 = 0,56%), Trichoplusia ni (Lepidoptera: Noctuidae) (LC 50 = 1,1%) 23 and the citrus mealybug, P. citri (LC 25 = 0.06%) 42 . The botanicals insecticides should be less toxic than synthetic insecticides, such as the thymol being 50 times less toxic to bees than the dimethoate 10 .…”
Section: Discussionmentioning
confidence: 76%
“…Carvacrol and thymol may inhibite the enzyme acetylcholinesterase, consequently leading to overstimulation of neurons in insects 39,40 . Oregano oil was the more toxic to A. mellifera, but with CLs higher for these pollinators than reported for the pests Anticarsia gemmatalis (Lepidoptera: Noctuidae) (LC 25 = 0.13%) 14 , Euproctis chrysorrhoea (Lepidoptera: Lymantriidae) (LC 50 = 0.05%) 22 , Thaumetopoea wilkinsoni Tams. (Lepidoptera: Thaumatopoeidae) (CL 50 = 0.31%) 41 and the citrus mealybug [Planococcus citri (Risso) (Hemiptera:Pseudococcidae)] (LC 25 = 0.06%) 42 .…”
Section: Discussionmentioning
confidence: 77%